The greatest science stories never told : 100 tales of invention and discovery to astonish, bewilder, & stupefy - Beyer, Rick, 1956-; History (Television network) (New York : Harper, 2009)
Contains one hundred anecdotes about a variety of inventions, such as the push-button phone, the stethoscope, and the space suit.
Adult
Keywords: Science -- Miscellanea; Science -- Miscellanea